2007
DOI: 10.1164/rccm.200610-1527oc
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia Causes Insulin Resistance in Lean Mice Independent of Autonomic Activity

Abstract: Rationale and Objectives: Although many clinical physiology and epidemiology studies show an association between obstructive sleep apnea (OSA) and markers of insulin resistance, no causal pathway has been established. The purpose of the current study was to determine if the intermittent hypoxia (IH) stimulus that characterizes OSA causes insulin resistance in the absence of obesity. Furthermore, we assessed the impact of IH on specific metabolic function in liver and muscle. Finally, we examined the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
233
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 319 publications
(264 citation statements)
references
References 49 publications
19
233
0
9
Order By: Relevance
“…Resolution of OSA with weight loss may contribute to weight loss-induced improvement in insulin resistance (41). Murine data indicate that intermittent hypoxia (IH) mediates the effect of OSA on insulin resistance (26,42). The impact of IH is further highlighted by our present findings, which demonstrate that insulin resistance is linked specifically to IH rather than to apnea periodicity (RDI).…”
Section: Osa Systemic Inflammation and Metabolic Dysfunction In Sevmentioning
confidence: 56%
“…Resolution of OSA with weight loss may contribute to weight loss-induced improvement in insulin resistance (41). Murine data indicate that intermittent hypoxia (IH) mediates the effect of OSA on insulin resistance (26,42). The impact of IH is further highlighted by our present findings, which demonstrate that insulin resistance is linked specifically to IH rather than to apnea periodicity (RDI).…”
Section: Osa Systemic Inflammation and Metabolic Dysfunction In Sevmentioning
confidence: 56%
“…Observational studies have also demonstrated that OSA is an independent risk factor for prediabetes and incident diabetes (10)(11)(12)(13). Both animal and human models of intermittent hypoxia and sleep fragmentation acutely mimicking OSA show evidence of insulin resistance and glucose intolerance (14)(15)(16)(17). Despite this strong association between OSA and alterations in glucose metabolism, there is still controversy as to whether treatment of OSA with continuous positive airway pressure (CPAP) has metabolic benefits (18,19).…”
mentioning
confidence: 99%
“…Intermittent hy poxia, a mo del of OSA, induces acute insulin resistance in healthy humans (9) and animals (10). Mice recei ving obesityinducing diets showed a greater increase of the HOMA index under intermittent hypoxia than lean mice (11).…”
Section: Introductionmentioning
confidence: 99%